2015
DOI: 10.1097/bcr.0000000000000139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Efficacy of Probiotic Administration Following Burn Injury

Abstract: Provision of probiotics has been limited postburn by questionable potential for bacterial translocation and risk of infection in an immune-compromised population. The purpose of this study was to evaluate the safety of probiotic administration in acutely burned, pediatric patients. Subjects were randomized to receive probiotic (n = 10) vs placebo (n = 10) twice daily. The investigational product was initiated within 10 days of burn, and daily supplementation continued until wound closure. Nursing staff was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 64 publications
2
39
0
1
Order By: Relevance
“…The dual pathophysiological states of inflammation and an altered skin microbiome in chronic wounds suggest a therapeutic potential for anti‐inflammatory drugs and probiotics in ameliorating both the psychological and biochemical comorbidities associated with chronic wounds. Indeed, in limited studies, oral and topical probiotics have improved healing in animals and humans with burns and ulcers . One study in rats showed probiotic kefir extracts improved healing in P. aeruginosa ‐infected burns more effectively than silver sulfadiazine application .…”
Section: Discussionmentioning
confidence: 99%
“…The dual pathophysiological states of inflammation and an altered skin microbiome in chronic wounds suggest a therapeutic potential for anti‐inflammatory drugs and probiotics in ameliorating both the psychological and biochemical comorbidities associated with chronic wounds. Indeed, in limited studies, oral and topical probiotics have improved healing in animals and humans with burns and ulcers . One study in rats showed probiotic kefir extracts improved healing in P. aeruginosa ‐infected burns more effectively than silver sulfadiazine application .…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae are able to out-compete normal commensal microbial species, specifically within the Firmicutes and Bacteroidetes phyla, and can perpetuate the effects of trauma and inflammation (33, 34). Research examining the efficacy of pre- and probiotics following burn injury has failed to show any significant benefits (35), which may be due to changes in the intestinal microenvironment following trauma that allow Gram-negative facultative bacteria to selectively outcompete beneficial commensal microbe colonization. The cause and consequence of Enterobacteriaceae overgrowth in our model remains to be established, and this will be the focus of future studies, as the relationship between the microbiome and intestine epithelial cells is highly important for homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalations of smokes are very rare in our patients. Nosocomial pneumopathies are, in general, a major cause of mortality and of morbidity in the burnt patients [9] [10]. They are highly linked to the initial severity of the burning and mostly supervene in burnt patients presenting lesions of inhalation and in those who underwent mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%